An improved efficiency by surface modification using pulse laser for partial transparent bifacial solar cell - Muhd Hatim Rohaizar,; Suhaila Sepeai,; Norasikin Ahmad Ludin,; Mohd Adib Ibrahim,; Kamaruzzaman Sopian,; Saleem H. Zaidi, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Bifacial solar cell has symmetrical configuration contacts on front and rear surface that eliminate expansion mismatch, decrease metal usage and improves photon absorption. The limitation of the reflector at the back of bifacial solar panel able to be eliminated by developing special designed partially transparent bifacial solar cell to optimize light trapping on rear surface. Therefore, the partial transparent silicon (Si) wafers were developed to increase light transmission to rear surface. Surface modification on Si wafer was conducted to form partial transparent Si wafer. Surface modification was employed by pulsed laser interaction to create dot marking array on Si wafer. Two pulsed laser power applied were 25.5W and 39.6W to produce pattern, then immersed in 10% KOH solution to etch laser-induced structure and debris to form partial transparent Si wafer. Low power laser was induced 80-85 µm depth of micro-hole, while high power was induced 140-145 µm. KOH treatment was conducted to etch laser region which to form deeper and wide micro-holes. The bifacial solar cells have been fabricated using partial transparent Si wafer and the current-voltage of the devices were tested. The front surface efficiency obtained for both partial transparent bifacial solar cells were 4.36% and 5.59%, while rear surface achieved 1.23% and 1.16%. Fabricated conventional bifacial solar cell has an efficiency of 2.39% for front and 0.64% for rear. The surface modification enhanced the efficiency due to the photon path length transmission to rear surfaces, micro-hole’s dimension and optical absorption in the near-infrared region.